The Role of Music in the Shadow Play "Hacivat and Karagöz" - Helvacı, Ayhan (European Journal of Social Science Education and Research, 2014)
The shadow play Hacivat and Karagöz has become an important part of the Traditional Turkish Theatre continuing for centuries. The existing shadow play which still preserves its popularity has become a significant entertainment tool for people. According to the local features of the performed characters and the content of the topic, this art type carried out by reflecting on a screen specially designed puppets from behind a lightened curtain and by playing with the voice of the performer has various music types and its instruments, especially Turkish folk music and Turkish classical music. in this study, within the play, the role of the music which is thought to form an important part of the shadow play was researched and the music and instruments used were analysed. The effect and role of the music within the play was particularly tried to be put forward.